Occupational rhinitis due to steel welding fumes. Issue 12 (25th September 2014) - Castano, Roberto; Suarthana, Eva
<x xml:space="preserve">Abstract</x> Exposure to welding fumes is a recognized respiratory hazard. Occupational asthma but not occupational rhinitis has been documented in workers exposed to steel welding fumes. We report a 26‐year‐old male with work‐related rhinitis symptoms as well as lower airways symptoms suggestive of occupational asthma and metal fume fever associated with exposure to steel welding fumes. The diagnosis of occupational rhinitis was confirmed by specific inhalation challenge. Am. J. Ind. Med. 57:1299–1302, 2014. © 2014 Wiley Periodicals, Inc.